Design optimisation of power generation in a vortex - induced vibration energy harvester - Chan, Ephraim Li Zan (2016)
Technological advancement in harnessing renewable energy has the potential of allowing humans to overcome the challenges of unsustainable energy consumption. New technologies are capable of harnessing the destructive vortex - induced vibrations (VIV) found from fluid flowing around submerged objects, and convert it into a source of energy. This report focuses on identifying the best design solution that serves the purpose of a Power Take-Off (PTO) - to convert mechanical movement to electrical energy. Through design optimisation, the PTO will be able to fulfill the project’s requirements, one of them being compatibility with a nonlinear spring system that enhances the VIV effect. The PTO designed and fabricated in this report consists of a gearing and generator system, and a magnetic induction system. The overall prototype to house the PTO and nonlinear spring system was also manufactured together with the PTO after much design iterations. The total cost for manufacturing and other areas of the prototype was approximately $4,616 which was within the budget given. Once the safety and the risks involved in the entire prototype were assessed, the PTO was then experimented on to compare the efficiency of each system. The testing was conducted manually instead of the prototype being submerged under flowing water. This was done to provide a cost-effective and safe method of testing. By considering the efficiency of the two systems after testing, the gearing and generator system and the magnetic induction system had an efficiency of 15.8% and 0.001% respectively. Hence the gearing and generator system should be implemented instead. The data findings of this project will prove useful for further prototype development, with more accurate and comprehensive testing done in the future.